Strategi, Peluang dan Tantangan Membangun Kerukunan Pemuda Di Era Milenial - M Thoriqul Huda (Satya Widya: Jurnal Studi Agama, 2020)
Abstract; Harmony becomes important in people's lives, especially in conditions of heterogeneous societies such as Indonesia, living in harmony in the community becomes a mandatory thing that must be in the midst of society. Indonesia, which consists of various tribes, religions and cultures, has tremendous potential for conflict if each individual cannot mature in understanding the reality of diversity. This research uses qualitative research methods, namely researchers conduct observations directly in the field, using various methods in data mining in the field such as interviews, observation, documentation, and data analysis. The object of research in this study is the East Java Inter-Religious Youth Communication Forum (FORKUGAMA), the interfaith youth forum that is interesting to study in the midst of the condition of the community that is being intensely examined with various SARA issues in recent years. In this study there were several findings that researchers found in the field including the strategies carried out by youth in building harmony, there were 4 points namely, strengthening social media networks, building interfaith youth discussion forums, instilling tolerance values ​​early and multiplying moderate narratives in religious. To realize this strategy, the community has important capital in building harmony, namely cultural factors, national factors, the role of religious elites, the role of politicians and the government, but there are also inhibiting factors in building harmony between the factors of political competition, the establishment of synagogues, abuse of religious symbols, deviant religious ideas, economics and public welfare and excessive modernization.